Risk Assessment in the Analysis of the Quality of Painting Works - V. I. Loganina; T. V. Uchaeva (Innovations in Science and Technology Vol. 2, 2022)
The issues of risk assessment of paint and varnish coatings of building products and structures are considered. A structural diagram of the reliability of protective and decorative coatings is presented as a combination of three elements connected in series, which are the coating itself, the contact layer and the substrate (plaster). Risk was considered as the likelihood of an event occurring with an adverse effect on the paintwork. In addition, the risk R was calculated as the expected damage Y as a result of the destruction of the coating. It is established, that the probability of adhesive failure of paint coatings is minimal. The value of risk as an expected damage as a result of adhesive destruction of coatings is 0.068-11.18 rubles per 1 m2, depending on the type of coating